THE RESULTS OF ENDOSCOPIC POLYPECTOMIES OF GULHANE GASTROENTEROLOGY CLINICS - K. DAĞALP; A. ALPER; N. KARAEREN; M. GÜLŞEN; S. BAĞCI; C. UYGURER; A. K. GÜRBÜZ; Levent DEMİRTÜRK (Turkish Journal of Gastroenterology, 2020)
-